PENGARUH GREEN ENTREPRENEUR ORIENTATION TERHADAP FIRM PERFORMANCE DENGAN MEDIASI GREEN INNOVATION - Abanan, Muchammad Zuhri Ramadhani; Susilowati, Christin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The escalating environmental problems has become a real threat for human, economic growth, and the environment itself. The sustainability of a business shall not be prioritized to profit only; it must also be achieved for environmental and social wellbeing as well as for dynamic changes. Green entrepreneurial orientation is a concept that carries strategic measures for environmentally-friendly business and sustainable business performance improvement. Further, green entrepreneurial orientation and green innovation are crucial concepts that must be applied by micro, small, and medium-sized entrepreneurs, particularly since MSMEs have more freedom and flexibility in innovation compared to larger companies. This research aims to analyze the effects of green entrepreneurial orientation on the performance of tempe chips business in Sanan of Malang City through the mediation of green innovation. The respondents of this explanatory research are 42 owners of MSMEs that are members of Sanan Tempe Chips Industrial Center Association in Malang City. The research instruments were assessed using validity and reliability tests, and the data was analyzed using Partial Least Squares. This study finds that green entrepreneurial orientation affects firm performance, that green innovation influences firm performance, and that green innovation mediates the influence of green entrepreneurial orientation on firm performance.